Integrating what and for whom? Financialisation and the Thames Tideway Tunnel. (August 2019) - Loftus, Alex; March, Hug
The Thames Tideway Tunnel (TTT), often referred to as the Thames super sewer, is currently one of the largest infrastructure projects underway in any European city. Costing an estimated £4.2 billion, the sewer connects London's Victorian sewerage network with the Thames Wastewater Treatment Works at Beckton. The latter facility has been described as the UK's Water–Energy–Food nexus poster child, for its combination of desalination facilities, green energy generation and wastewater treatment. While physically connected to the Beckton plant, the TTT is, paradoxically, designed with an apparent disregard for the water–energy nexus. If the Beckton plant represents a nexus-based vision of integration – what Macrorie and Marvin (2016) refer to as Mode 2 Urban Integration – the TTT harks back to a view of urban integration carried from the Victorian era through to the present moment. What unites the two projects, and what undergirds the transformation of the hydrosocial cycle, is a financial model more focused on the extraction of rents from Thames Water's consumers. Thames Water's dismissal of genuinely integrated alternatives appears guided more by the financialisation of the urban integrated ideal than by what is needed to respond to London's broader environmental needs. Contesting the project, therefore, will involve slicing through the various claims to integration, going beyond the many proposals for evidence-based alternatives, and capturing the transformations being wrought by finance's entry into infrastructure provision.